Ikhtilaf dalam Tafsir Al-Qur’an dan Kedudukannya dalam Hukum Islam: Ikhtilaf in the Tafsir of the Qur'an and its Position in Islamic Law - Muhammad Ikhsan; Azwar, Azwar (Litera Academica Publishing, 2024)
This study aims to describe the types of ikhtilaf that occur in the interpretation of the Qur'an based on the factors that cause the ikhtilaf and its position in Islamic law. This study uses a qualitative method with a content analysis approach. The results of this study indicate that based on the causal factors, ikhtilaf consists of: ikhtilaf based on the text (tafsir bi al-ma'ṡūr) and ikhtilaf based on other than the text (tafsir bi al-ra'yi). Ikhtilaf based on the text tends to be varied (ikhtilāf tanawwu'), reflecting flexibility and the ability to adapt in the application of Islamic law according to various contexts and situations. In contrast, ikhtilaf based on other than the text is often contradictory (ikhtilāf taḍāḍ), indicating that there is room for ijtihad and diverse interpretations in complex situations. However, due to its contradictory nature, this ikhtilāf often requires a deeper resolution to reach consensus or at least tolerance of the differences.